An equivalence theorem for regular differential chains. (July 2019) - Boulier, François; Lemaire, François; Poteaux, Adrien; Moreno Maza, Marc
Abstract: This paper provides new equivalence theorems for regular chains and regular differential chains, which are generalizations of Ritt's characteristic sets. These theorems focus on regularity properties of elements of residue class rings defined by these chains, which are revealed by resultant computations. New corollaries to these theorems have quite simple formulations.